Self-assembly of functionalized Echinops-like Rh porous nanostructure electrocatalysts for highly efficient seawater splitting. Issue 26 (18th June 2021) - Jiang, Xue; Dong, Zemeng; Wang, Jing; Zhang, Ning; Xu, Guang-Rui; Zhang, Wen; Lai, Jianping; Li, Zhenjiang; Wang, Lei
Abstract : The electrolyzer assembled with bifunctional Echinops-like Rh PNNS catalysts exhibited a low cell voltage of 1.61 V at 10 mA cm −2, which is superior to that of Pt black‖RuO2 couples. Abstract : Although water electrolysis provides a promising technology for global hydrogen economics, highly efficient electrocatalysts are required to boost the sluggish kinetics of both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) under neutral conditions. Herein, we synthesized novel polyethyleneimine (PEI) functionalized Echinops-like Rh porous nanostructures (Echinops-like Rh PNNSs) by a solvothermal method, which originated from the self-assembly of Rh two-dimensional (2D) sub-nanoflakes with 1.2 nm thickness. As a good electron donor, −NH2 on PEI could modulate the electronic structure of Echinops-like Rh PNNSs, reducing the adsorption energy of H2 O on the surface of Echinops-like Rh PNNSs. Meanwhile, −NH2 groups could specifically enrich H2 O molecules under neutral conditions, which facilitates water splitting. The as-synthesized Echinops-like Rh PNNSs exhibit high HER activity with ultralow overpotential, low Tafel slope, and excellent stability. Moreover, the Echinops-like Rh PNNSs also showed an enhanced OER activity than commercial RuO2 with a small overpotential of 79.5 mV at 10 mA cm −2 in neutral media. When using Echinops-like Rh PNNSs as both anode and cathode catalysts for overall seawater splitting, a cell voltage of only 1.61 V is needed for generating 10 mA cm −2 current density, greatly boosting the efficiency of seawater splitting.